Delayed Latency of Postural Muscles of Individuals with Intellectual Disabilities - Tolentino-Castro, J. Walter; Mühlbeier, Andreas; Mochizuki, Luis; Wagner, Heiko (Frontiers in Psychology, 2018)
3 Individuals with intellectual disabilities (ID) (50 < IQ > 79) show impaired motor and postural 4 control, these impairments are highly related to falls and injuries. Recent studies demonstrated 5 these impairments are related with fine and gross motor development, which are more strongly 6 associated with cognition, and consequently language for individuals with ID than for without 7 ID. Despite these studies, little is known about the structure and functioning of this population’s 8 spinal cord, which is highly involved in postural control. The aim of our study was to assess the 9 latency of the reflex responses in postural muscles after unexpected lateral external perturbations, 10 in individuals with intellectual disabilities compared to typically developed participants. We 11 assessed 16 participants with intellectual disabilities, 9 males and 7 females, (aged 24.06 ± 8.66 12 years) and 20 typical developed participants (CG), 11 females, 9 males, (aged 21.20 ± 1.96 13 years). While the participants were in an upright standing position electromyography was used 14 to collect data from M. obliquus externus abdominis (OE) muscles, which were activated by 15 unpredictable perturbations applied by a servomotor on a hand-held grip, following the lateral 16 external perturbation to the trunk. The intellectual disabilities group presented contralateral OE 17 muscles latency of 85.71 ± 27.24 ms, and CG group presented 68.62 ± 10.25 ms, no differences was 18 found. Ipsilateral OE muscles latency also did not differs between the groups, ID group showed 19 96.60 ± 30.20 ms and CG group showed 95.57 ± 33.53 ms. Our study furthers the knowledge about 20 the muscular activity of individuals with intellectual disabilities. The present experimental results 21 may suggest unique spinal cord processing of individuals with intellectual disabilities when they 22 are faced with unexpected lateral external perturbations.